Interest- and Talent-Based Student Management: Strategies for Achieving International Research Achievements at MAN 1 Jembrana - M. Dzikri Chandra; Ferdinan Dwi Abdurrahman; Apriliana Nayla Zahratusshiefa; Fadia Ainur Fitri; Arditya Prayogi (Journal of Islamic Elementary Education, 2026)
The dynamics of madrasa education in the global era require a transformation from conventional academic orientation to the creation of an innovative research ecosystem. However, youth scientific extracurriculars often face challenges with sporadic achievement regeneration and a lack of verification instruments to measure students' independent research understanding. This community service aims to restructure interest and talent-based student management at MAN 1 Jembrana. The program utilized a Participatory Action Research (PAR) method involving 5 mentoring teachers and 45 target students. The intervention stages included proactive recruitment (talent scouting), Problem-Based Learning (PBL)-based research incubation, cognitive validation through mock defense, and the institutionalization of peer-mentoring. The results demonstrated a 93.4% surge in students' understanding of research methodology and successfully eliminated teacher dominance that triggers the pseudo-researcher phenomenon. The new research ecosystem was also proven capable of incubating innovation prototypes based on local wisdom. This program concludes that a structured, collegial, and autonomous student management model is crucial in maintaining the sustainability of madrasa achievements in international-level research competitions.